Macromineral requirements of Dorper×thin-tailed Han crossbred female lambs - Shou-kun JI; Gui-shan XU; Qi-yu DIAO; Kai-dong DENG; Cheng-gang JIANG; Yan TU; Nai-feng ZHANG (Journal of Integrative Agriculture)
A comparative slaughter trial was conducted to determine the net mineral requirements for maintenance and growth of Dorper crossbred female lambs raised from 20 to 35 kg of body weight (BW). Thirty-five Dorper×thin-tailed Han crossbred female lambs of (20.3±1.14) kg BW were used: 7 lambs were randomly chosen and slaughtered at the beginning of the experiment as the baseline group for measuring the initial body composition; another 7 lambs were randomly chosen and offered a pelleted mixed diet ad libitum and slaughtered at (27.0±0.73) kg BW; the remaining 21 lambs were randomly divided into 3 groups of 7 animals each and subjected to the same diet either ad libitum or at 70 or 40% of ad libitum intake. The 21 lambs were fed in 7 slaughter groups, with each group consisting of one lamb from each treatment (ad libitum, 70 or 40% of ad libitum intake). The 3 groups were slaughtered when the sheep fed ad libitum attained (33.8±0.52) kg of BW. The body composition of five minerals (Ca, P, Na, K, and Mg) was determined. The net mineral requirements for maintenance were 35.01, 25.18, 9.30, 31.35, and 2.03 mg kg−1 empty BW (EBW) for Ca, P, Na, K, and Mg, respectively, and the net growth requirement per kg of EBW gain ranged from 9.73 to 8.87 g of Ca, 5.83 to 5.27 g of P, 1.73 to 1.63 g of Na, 3.73 to 4.08 g of K, and 0.26 to 0.25 g of Mg for Dorper crossbred lambs in China, respectively. The estimates of mineral requirements with Dorper crossbred lambs in the current study were not consistent with the recommendations from previous studies.